Computerized Accounting Systems and Financial Reporting in Commercial Banks: Case Study of Stanbic Bank Soroti Branch - Faith Tabitha Acam (Uganda Christian University, 2024)
This research report was undertaken to investigate the effect of computerized accounting systems and financial reporting of Stanbic Bank Soroti branch. It was guided by three objectives; to examine the effect of the usage of Tally on the financial reporting of Stanbic Bank Soroti branch, to assess the relationship between Quick books and financial reporting of Stanbic Bank Soroti branch, to investigate the effect of spread sheets on financial reporting of Stanbic Bank Soroti branch. The researcher used a sample size of 36 respondents then used questionnaires and interview guide to collect data which was later analyzed using the statistical package for social sciences. Results of the first objective shows that usage of Tally positively (Beta=0.153) predicts the financial reporting of Stanbic Bank Soroti branch and effect is significant at p-value < 0.05.by 9.6%, Supported by the following responses; 44% strongly agreed, 22% Agreed to the statement that the software's automatic calculation features and real-time updating capabilities prevent errors often associated with manual calculations and paper-based systems; 25% strongly agreed, 19% to the statement that tally's built-in reconciliations and reporting functionalities expedite the preparation of financial statements, freeing up time for accountants to focus on more analytical tasks, 42% strongly agreed, 8% agreed to the statement that tally's provision of real-time cash flow and profitability data allows businesses to make informed financial decisions promptly. Results of the second objective showed that Quick books on positively (Beta=0.224) predicts the financial reporting of Stanbic Bank Soroti branch and effect is significant at p-value < 0.05.by 7.7% and was supported by the following responses which include; 14% strongly agreed, 28% agreed to the statement that QuickBooks enables managers to generate reports that provide deep insights into profitability, liquidity, and financial health, 44% strongly agreed, 11% Agreed to the statement that QuickBooks can enable businesses to maintain accurate records and generate timely financial reports for internal and external stakeholders while results of the third objective indicated that spread sheets (Beta=0.091) predicts and affects their financial reporting of stanbic Bank Soroti branch.. However, its effect is insignificant at p-value > 0.05 by 2.1% and supported by the following: 14% strongly agreed, 47% agreed to the statement that the emergence of cloud-based spreadsheet applications has improved collaboration and real-time data access. The bank should conduct regular training sessions for employees to ensure they are proficient in using Tally. This includes understanding the software's functionalities, updates, and best practices for financial reporting, Customize Tally to suit the specific needs of the organization.
Undergraduate research